Pembangunan Sistem Informasi Manajemen Penjualan CV. Mitra Teknik Berbasis Web - Mohamad Reza Mawardi; Faizatul Amalia; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Competition is increasingly competitive in today's industrial environment. Companies must be able to find and identify the factors that are the key influences for success. The development of technology is very influential on the strength of a company to compete in a climate of competition between competitors. CV. Mitra Teknik is a company engaged in manufacturing that serves a services, sales, repair of machinery materials industry. In running this business, CV. Mitra Teknik need a system that can manage data and information within a company to run its industrial wheels. However, current business processes that are running such as recording each transaction are still recorded manually in the company book, this can disrupt the daily operations of the company. The solution to solve the problem is by making a sales management information system. With the construction of the sales information system, it is expected to be able to provide convenience for users in data processing so that it can save time in running the company's business processes. From test conducted using white-box testing, the test gained 100% success rate, for black-box testing that tests the system validation successfully obtained a value of 100%. And the results of the User Acceptance Testing (UAT) in the calculation that has been done by 4 validators obtained values ​​above 75%, which according to the system rating scale table declared capable of being understood by the user.